INFILTRATE PULMONARY TUBERCULOSIS, GASTRIC ULCER AND HIV INFECTION (COMORBIDITY AND MULTIMORBIDITY) - E. S. Skvortsova; E. A. Borodulina; A. M. Osadchuk (Туберкулез и болезни лёгких)
Peptic ulcer is registered in 20,5% of those suffering from infiltrate pulmonary tuberculosis and in 19,5% of HIV patients at C2 stage, ill with infiltrate pulmonary tuberculosis and presenting complaints about dyspeptic disorders. The following is typical of multimorbidity of pulmonary tuberculosis, HIV infection and peptic ulcer: oligosymptomatic start of tuberculosis, asthenic syndrome dominating among clinical symptoms, manifestations of gastric and intestinal indigestion, weight loss (2-4 times more often compared to HIV negative patients), less expressed lung tissue destruction (2 time less compared to HIV negative patients). H. pylori is a causative agent of the peptic ulcer in 62,5% of patients with infiltrate pulmonary tuberculosis and in 58,7% of HIV infected patients at C2 stage, suffering from pulmonary tuberculosis. Comorbidity of H. pilori negative peptic ulcer and infiltrate pulmonary tuberculosis differs from comorbidity of H. pilori positive peptic ulcer and infiltrate pulmonary tuberculosis since the first has confidently true unfavorable forecast of the outcome.